Every trainer's handbook - Agochiya, Devendra (SAGE, 2009)
Every Trainer's Handbook (Second Edition) is a practical guide that takes the reader through a step-by-step process of planning, organising and delivering an effective training programme. It offers concrete suggestions and guidelines to trainers for enhancing their knowledge and competencies while simultaneously engaging them in a substantive discussion on various concepts, theories and issues related to training. This new edition of the book enlarges the scope of the previous edition. Underscoring the importance of a cohesive and synthesised approach, it brings together all interrelated aspec.